Doxycycline Proniosomal Gel as Local Drug Delivery System in Periodontal Disease: A Vitro Study - Dhawal Rajendra Mody; Vrushali Lathiya; Abhay P. Kolte; Vaishnavi Biradar; Vaishnavi Langde (Journal of Pharmacy and Bioallied Sciences)
Background: Periodontitis is an inflammatory condition of the oral cavity in which microorganisms play a significant role in the pathogenesis and onset. The host immune system starts as an inflammatory process in response to microbial attack that protects and kills the periodontium. Doxycycline is a semi-synthetic variant of tetracycline that is made from oxytetracycline. Doxycycline inhibits the production of both aerobic and anaerobic microbial protein through its potent activity against both Gram-positive and Gram-negative bacteria. Materials and Methods: The preparation method of doxycycline proniosomal gel involved accurately weighing doxycycline and all excipients (12 Batches). Doxycycline was mixed with 1 ml of ethanol, and all the excipients, like surfactant, lecithin, cholesterol, were added in precisely weighed amounts. The characterization of proniosomal gel and determination of drug entrapment efficacy is calculated. Result: Doxycycline release from the doxycycline proniosomal gel (Batch F12) was studied using Franz diffusion cell assembly with dialysis membrane for 7 days in phosphate-buffered saline (7.4) indicated sustained release of doxycycline from the formulation. Conclusion: Proniosome containing doxycycline may therefore be a locally effective drug delivery method for treating periodontitis. Current in vitro study is mainly focused on preparation of proniosomal gel containing doxycycline as local drug delivery system in periodontal disease.